Supplementation of vitamin E and omega-3 fatty acids during the early posthatch period on intestinal morphology and gene expression differentiation in broilers - Ji Wang; Daniel L. Clark; Sheila K. Jacobi; Sandra G. Velleman (Poultry Science, 2021)
Early posthatch nutrition is important for gut health. Vitamin E (VE) and omega-3 (n-3) fatty acids can improve gut health through antioxidative and anti-inflammatory effects. The objective of this study was to identify the effects of VE, n-3 fatty acids, and combination of both during the starter phase (0–10 d) or grower phase (11–24 d) on intestinal morphology and expression of genes associated with gut health. A total of 210 Ross 708 broilers were randomly assigned into 7 treatments with 10 replicates of 3 birds each. The control group was fed a corn–soybean meal–basal diet during the entire study (0–58 d). Supplementation of VE (200 IU/kg), n-3 fatty acids (n-6/n-3 ratio of 3.2:1), and combination of both were fed during the starter phase (0–10 d) or grower phase (11–24 d). All of the broilers were harvested at 58 d of age. Villus height, crypt depth, villus width, distance between villi, and number of intraepithelial lymphocytes were obtained. Expression of 21 genes was measured using NanoString analysis. Expression of solute carrier family 15 member 1 (P = 0.01) associated with peptide transport and mucin 2 (P = 0.03) related with intestinal mucus barrier was increased in the broilers supplemented with n-3 fatty acids in the grower diet compared with the control. Expression of solute carrier family 7 member 1 associated with amino acid transport was decreased in the group supplemented with n-3 fatty acids during the starter phase compared with the group supplemented with n-3 fatty acids (P = 0.01) or VE and n-3 fatty acids during the grower phase (P = 0.03). These data suggest that VE and n-3 fatty acids supplemented during the grower phase have a positive effect on improving nutrient transport with n-3 fatty acids supplementation in the grower diet showing the most beneficial effect. These findings can be used in the development of nutritional management strategies to improve broiler growth performance and meat quality.